Platelet GPIIb supports initial pulmonary retention but inhibits subsequent proliferation of melanoma cells during hematogenic metastasis - Echtler, Katrin; Eichhorn, Martin E. (PLOS ONE, 2017)
Platelets modulate the process of cancer metastasis. However, current knowledge on the direct interaction of platelets and tumor cells is mostly based on findings obtained in vitro. We addressed the role of the platelet fibrinogen receptor glycoprotein IIb (integrin αIIb) for experimental melanoma metastasis in vivo. Highly metastatic B16-D5 melanoma cells were injected intravenously into GPIIb-deficient (GPIIb-/-) or wildtype (WT) mice. Acute accumulation of tumor cells in the pulmonary vasculature was assessed in real-time by confocal videofluorescence microscopy. Arrest of tumor cells was dramatically reduced in GPIIb-/- mice as compared to WT. Importantly, we found that mainly multicellular aggregates accumulated in the pulmonary circulation of WT, instead B16-D5 aggregates were significantly smaller in GPIIb-/mice. While pulmonary arrest of melanoma was clearly dependent on GPIIb in this early phase of metastasis, we also addressed tumor progression 10 days after injection. Inversely, and unexpectedly, we found that melanoma metastasis was now increased in GPIIb-/- mice. In contrast, GPIIb did not regulate local melanoma proliferation in a subcutaneous tumor model. Our data suggest that the platelet fibrinogen receptor has a differential role in the modulation of hematogenic melanoma metastasis. While platelets clearly support early steps in pulmonary metastasis via GPIIb-dependent formation of platelet-tumor-aggregates, at a later stage its absence is associated with an accelerated development of melanoma metastases.
Gesehen am 21.11.2018